1959
DOI: 10.1107/s0365110x59000408
|View full text |Cite
|
Sign up to set email alerts
|

Structure and growth of beryllium oxide on single crystal of beryllium

Abstract: The nature of the structure and growth of BeO films formed by heating single crystals of beryllium in air over a wide range of temperatures was studied in detail using electron diffraction, and electron microscopy.The epitaxial nature of the oxide formed in the temperature range 300 °C. to 400 °C. on a Be (001) cleavage face was established.In the case of electropolished (001) surfaces of beryllium, it was found that the epitaxial BeO overgrowth was less well-defined. It was suggested that this disorientation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1963
1963
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Both materials have lattices with hexagonal symmetry (hcp for Be and wurtzite for BeO). The experimental study of the growth of BeO on top of Be(0 0 0 1) with electron diffraction and electron microscopy suggests that the first stage of BeO growth is in the ⟨0 0 0 1⟩ direction with ⟨1 0 0 0⟩ of Be and BeO being parallel [30]. Thus, in our study we will first build interfaces between Be(0 0 0 1) and BeO(0 0 0 1) that satisfy these conditions.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Both materials have lattices with hexagonal symmetry (hcp for Be and wurtzite for BeO). The experimental study of the growth of BeO on top of Be(0 0 0 1) with electron diffraction and electron microscopy suggests that the first stage of BeO growth is in the ⟨0 0 0 1⟩ direction with ⟨1 0 0 0⟩ of Be and BeO being parallel [30]. Thus, in our study we will first build interfaces between Be(0 0 0 1) and BeO(0 0 0 1) that satisfy these conditions.…”
Section: Introductionmentioning
confidence: 90%
“…Experiments of BeO growth on Be suggest that at the Be(0 0 0 1)/BeO(0 0 0 1) interface, ⟨1 0 0 0⟩ directions of Be and BeO are parallel [30]. However, there is a mismatch between both lattice constants in this direction: a Be = 2.25-2.32 Å [31] and a BeO = 2.698-2.766 Å [32].…”
Section: Methodsmentioning
confidence: 99%
“…The growth and properties of whiskers of a great number of metals (including beryllium) have been studied [7,8]. The mechanism of whisker formation on beryllium is still unknown but it is clear that the threads (without the balls) start to grow under oxidation of beryllium in air [8] meaning that the whisker thread growth is a way to form beryllium oxide on the beryllium surface. The typical Table 1 Thickness of beryllium oxide surface layer on beryllium pebbles as a result of the evaluation of the oxygen spectra from Fig.…”
Section: Sem Examination Of Pebbles Surfacementioning
confidence: 99%
“…Beryllium oxidation below ~1000 °C is believed to follow parabolic rate law, whereas at the temperature beyond this -linear rate law [5]. In early studies of V. D. Scott on beryllium oxidation mechanism few beryllium oxide nano-rods grown around disorders of beryllium lattice were observed [6]. Author suggested that these disorders may take the form of screw dislocations parallel to the axis of the rod.…”
Section: Introduction *mentioning
confidence: 99%